Plasma micro-RNA biomarkers for diagnosis and prognosis after traumatic brain injury: A pilot study. (April 2017) - Mitra, Biswadev; Rau, Thomas F.; Surendran, Nanda; Brennan, James H.; Thaveenthiran, Prasanthan; Sorich, Edmond; Fitzgerald, Mark C.; Rosenfeld, Jeffrey V.; Patel, Sarjubhai A.
Highlights: Blood biomarkers can assist in diagnosis of mild traumatic brain injury. Biomarkers could inform medical counselling of at-risk individuals. Two micro-RNAs demonstrated potential clinical utility. Abstract: Prediction of post-concussive syndrome after apparent mild traumatic brain injury (TBI) and subsequent cognitive recovery remains challenging, with substantial limitations of current methods of cognitive testing. This pilot study aimed to determine if levels of micro ribonucleic acids (RNAs) circulating in plasma are altered following TBI, and if changes to levels of such biomarkers over time could assist in determination of prognosis after TBI. Patients were enrolled after TBI on presentation to the Emergency Department and allocated to three groups: A – TBI (physical trauma to the head), witnessed loss of consciousness, amnesia, GCS = 15, a normal CT Brain and a recorded first pass after post-traumatic amnesia (PTA) scale; B TBI, witnessed LOC, amnesia, GCS = 15, a normal CT brain and a PTA scale test fail and: C – TBI and initial GCS <13 on arrival to the ED. Venous blood was collected at three time points (arrival, day 5 and day 30). Isolation of cell-free total RNA was then assayed using a custom miRNA PCR array. Two micro-RNAs, mir142-3p and mir423-3p demonstrated potential clinical utility differentiating patients after mild head injury into those at greater risk of developing amnesia and therefore, post-concussive syndromes. In addition, these miRNA demonstrated a decrease in expression over time, possibly indicative of brain healing after the injury. Further evaluation of these identified miRNA markers with larger patient cohorts, correlation with clinical symptoms and analysis over longer time periods are essential next steps in developing objective markers of severity of TBI.